Comparison of zirconia degradation in dental implants and femoral balls: an X-ray diffraction and nanoindentation study - Javier Gil; José Angel Delgado-; Eugenio Velasco-Ortega; Begoña Bosch; Luis Delgado; Román Pérez-Antoñanzas; Mariano Fernández-Fairén (SpringerOpen, 2021)
Abstract Background New tetragonal zirconia polycrystal dental implants stabilized with yttria (Y-TZP) have appeared in the implantology market in the form of single piece or two-piece zircona implant system. These new type of implants improve the aesthetical properties compared to conventional commercially pure (c.p.) titanium used for implants, although the long term mechanical behavior of these new implants is not yet well known. In orthopaedics, the application of zirconia as femoral balls presented an important controversial use due to the premature fracture once implanted. Y-TZP dental implants can be affected by hydrothermal degradation and its behavior should be analysed to avoid a premature fracture. The scientific question behind the study is to analyse if the degradation mechanism observed in orthopaedics applications of Y-TZP is similar to that of Y-TZP for dental applications. Materials and methods For this purpose, 30 original Y-TZP dental implants and 42 Y-TZP femoral balls fractured in vivo have been studied. Dental implants were submitted to an accelerated hydrothermal degradation to compare with the femoral balls fractured in vivo. Phase transformation as well as the mechanical behaviour of the degraded samples was studied by X ray diffraction and nanoindentation tests, respectively. Results Results have shown that the fracture mechanism of dental implants does not resemble the mechanism observed in orthopaedic samples, presenting a good long-term behaviour. Conclusion The results ensure the good performance of zirconia dental implants, because the degradation of the ceramic is very limited and does not affect the mechanical properties.